La Mesopotamia - Lynch, Guillermo P. J. (Buenos Aires)
Signatura: 0/35
Existencia: 1919- 1(1-10); 1920- 1(11-23), 2(24-31); 1921- 2(32-39)
Keywords: Argentina; Misiones; Ciencias Sociales; Corrientes-Argentina; Entre Rios